The relationship between driver's background and driver's speed preferences - Nurul Farhana, Nasarrudin (2016)
Nowadays, road accidents are common issues in the newspapers every day. The number of road accident cases increases year by year in Malaysia. According to statistics by Malaysian Institute of Road Safety Research, speeding is the second highest (21%) factors that contribute to crash. The aim of the study are to determine the speed preferences of the road users based on the environments of the road, to investigate the relationship between driver‟s background and driver‟s speed preferences, and to determine the difference between speed preferred by road users and the actual speed they used. A set of questionnaire was distributed to 90 respondents in University of Malaysia Pahang which consist of a variety of questions on gender, age, driving experience, classes of driving license, daily transportation, occupation, distance of residence to workplace and estimated driving hour for a day to get the driver‟s speed preferences. A radar gun was used to obtain the actual speed that road users used. The study areas are located at Federal Road 2 from KM3 until KM27. The result of this study showed that male drivers prefer to use higher speed compare to female drivers, the drivers aged below 50 years old prefer to use higher speed than drivers aged above 50 years old, the drivers who have driving license less than 5 years prefer to use slower speed, licensee for both classes B2 and D prefer to use higher speed compare to single license holder which is license B2 or D, car drivers prefer to use higher speed than motorcycle rider, the drivers with longer distance to workplace prefer to use higher speed and drivers with longer estimated driving hour will choose the higher speed. Other than that, the driver‟s speed preferences at each point have been identified where at point 1 is 80-90 km/hr, point 2 is 60-70 km/hr, and point 3 is 50-60 km/hr and lastly at point 4 is 80-90 km/hr. The result from cumulative frequency based on speed at 85th percentiles, point 1 is 55 km/hr, point 2 is 90 km/hr, point 3 is 60 km/hr, and point 4 is 85 km/hr. In conclusion, this finding shows that driver‟s background imposed serious effects towards driver‟s speed preferences. Further research focusing on driver‟s background could be proposed in order to minimise contributing of speed as crash factors.